EKSTRAK ETANOL BIJI ALPUKAT (Persea americana Mill.) DAN EKSTRAK ASETON DAUN YAKON (Smallanthus sonchifolius) SAMA EFEKTIFNYA DALAM MENURUNKAN KADAR GULA DARAH TIKUS YANG DIINDUKSI ALOKSAN - Dylan Putra; Jojor Lamsihar Manalu (Bahasa Indonesia, 2020)
Introduction: Diabetes mellitus is a disease that affects many people globally, including Indonesia. The prevalence of diabetics in Indonesia increased from 6.9% (2013) to 8.5% (2018). Herbs can be used to lower the glucose concentration, including avocado seeds and yacon leaves that contain flavonoids and astringent compounds.The aim of the study to see the comparison of the effectiveness of avocado seeds extract and yacon leaves extract in reducing blood sugar levels in rats.Methods: This research was an experimental study using rat as animal model. Rats were divided into groups which were given ethanol extract of avocado seed (Persea americana Mill.) and acetone yacon leaf extract (Smallanthus sonchifolius) with various doses i.e. 150mg/kg, 300mg/kg, and 450mg/kg. The rat was given alloxan to induce blood sugar levels increase and the results were observed 2 days before administration of the extract for 5 days. The extraction process was done by maceration method. Data was analysed using One Way Anova.Results: There was a decline in blood sugar levels in each group given the avocado seed extract and yacon leaf extract . However, there was no statistical difference in effectiveness between the extracts.Conclusion: Both avocado seed extract and yakon leaf extract are equally effective in decreasing blood sugar levels in alloxan-induced rats.